2017
DOI: 10.1021/acs.jpcc.7b06963
|View full text |Cite
|
Sign up to set email alerts
|

Sequentially Deposited Antimony-Doped CH3NH3PbI3 Films in Inverted Planar Heterojunction Solar Cells with a High Open-Circuit Voltage

Abstract: We introduce antimony-doped hybrid perovskite compounds in planar inverted solar cells. Here, we report in-depth and systematic studies on the formation of the perovskite layer through a modified two-step spin-coat method. In this method, the “loading time” of CH3NH3I on a “wet” PbI2 layer was varied in achieving a complete conversion to the perovskite material. The “loading time” that in turn also controlled morphology of the perovskite layer along with the antimony content in perovskite compounds was varied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…The year after, Chatterjee et al developed a modified two‐step method to fabricate efficient ITO/NiOx/MAPb 1− x Sb x I 3 /PCBM/Al PSCs. [ 44 ] In a classic two‐step method, MAI is dropped on a dried PbI 2 layer (Section 2.3.2). The authors dropped MAI on a wet PbI 2 .…”
Section: Other Substitutions For Lead‐less Pscsmentioning
confidence: 99%
See 1 more Smart Citation
“…The year after, Chatterjee et al developed a modified two‐step method to fabricate efficient ITO/NiOx/MAPb 1− x Sb x I 3 /PCBM/Al PSCs. [ 44 ] In a classic two‐step method, MAI is dropped on a dried PbI 2 layer (Section 2.3.2). The authors dropped MAI on a wet PbI 2 .…”
Section: Other Substitutions For Lead‐less Pscsmentioning
confidence: 99%
“…Other materials such as group 2, 13, 14, and 15 elements and transition‐metal elements are also promising candidates for partial substitution of lead in PSCs. [ 44–48 ]…”
Section: Introductionmentioning
confidence: 99%
“…Band‐alignment at the hole‐collecting interface, that is, HTL/MAPbI 3 , needs attention for hole‐transports without any energy barrier. Following our earlier report on differential tunnel conductance and thereby DOS of the MAPbI 3 and transport‐layers in general, we could draw the energy‐level diagram of the complete device, namely, Cu@NiO/MAPbI 3 /Bi@PbS/PCBM for a 3% bismuth content. As can be seen from the diagram (Figure b), the 4% Bi@PbS would form a type‐I band‐alignment with PCBM.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to the above results, further increasing the Sb contents (up to 4%), the PCE of a device was reduced to 12.4%, which was even smaller than the PCE (13.1%) of pure MAPbI 3 perovskite. Subsequently, Chatterjee et al [ 90 ] reported Sb‐doped less toxic HPVKs (MAPb 1− x Sb x I 3 ). It was revealed both theoretically and experimentally that Sb doping altered the band structure of the perovskites, which was correlated with the improved device performance.…”
Section: Hpvksmentioning
confidence: 99%